A Note on Infinite Type Germs of a Real Hypersurface in - Nguyen, Thi Kim Son (H. : ĐHQGHN, 2019)
The purpose of this article is to show that there exists a smooth real hypersurface germ of D'Angelo infinite type in such that it does not admit any (singular) holomorphic curve that has infinite order contact with at . 2010 Mathematics Subject Classification. Primary 32T25; Secondary 32C25